Analysis of Marketing Strategy and Responsibility in J&T Express Delivery in Ajamu Area, Panai Hulu District, Labuhanbatu Regency, North Sumatera Province - Sari, Rida Kurnia (Garuda Prestasi Nusantara Consulting, 2025)
Indonesia has experienced remarkable development in terms of technological advancement, especially in e-commerce. The public now has more options for using courier services thanks to the growth of e-commerce. One of the courier services directly connected with Shopee is J&T Express. However, J&T Express is still often complained about by customers regarding delivery obstacles. Therefore, J&T Express needs to pay attention to the quality of service and the responsibilities provided so as not to harm consumers. The purpose of this research is to analyze the marketing strategies and responsibilities in J&T Express's delivery services. This research uses a qualitative approach in empirical legal research. The aim is to study the rules, identify them, and adapt them to the conditions on the ground. The results show that the J&T Express delivery process begins with the buyer inputting their checkout data, including the shipping address and package observations, before the J&T Express operational team sends the buyer's package. Some of the issues faced by J&T Express include delays in delivery, customer stock in the expedition warehouse, and damage to goods, which refers to physical damage or loss of package contents. To address the issue of shipping goods or packages, some solutions that can be implemented include regularly providing gifts or cash back as compensation. Keywords: strategy, responsibility, delivery